2011
DOI: 10.1016/j.gde.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy genetics—past, present, and future

Abstract: Human epilepsy is a common and heterogeneous condition in which genetics play an important etiological role. We begin by reviewing the past history of epilepsy genetics, a field that has traditionally included studies of pedigrees with epilepsy caused by defects in ion channels and neurotransmitters. We highlight important recent discoveries that have expanded the field beyond the realm of channels and neurotransmitters and that have challenged the notion that single genes produce single disorders. Finally, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 76 publications
(41 reference statements)
1
98
2
4
Order By: Relevance
“…This mixed group highlighted the potential flexibility of this system in an era of evolving understanding of the pathophysiology of epilepsies. For instance, for Nonlesional temporal lobe epilepsies (13,5) familial TLEs, our evolving understanding of the genetic influences based on twin and family data 25,29,30 suggests that this group would be better placed in the genetic group. Similarly, our evolving understanding of IPOE supports a genetic basis for this disorder.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation
“…This mixed group highlighted the potential flexibility of this system in an era of evolving understanding of the pathophysiology of epilepsies. For instance, for Nonlesional temporal lobe epilepsies (13,5) familial TLEs, our evolving understanding of the genetic influences based on twin and family data 25,29,30 suggests that this group would be better placed in the genetic group. Similarly, our evolving understanding of IPOE supports a genetic basis for this disorder.…”
Section: 10mentioning
confidence: 99%
“…12 This framework, which is not yet a formal scientific classification, provides flexible concepts that better reflect our current understanding of epilepsies, 12 especially in genetics. 13 Channelopathies are a major known mechanism in idiopathic epilepsies, [14][15][16] but non-ion channel genes such as LGI1, 17 SLC2A1, 18,19 and DEPDC5 20 are also important causes of Mendelian epilepsies. Susceptibility alleles are much more challenging to confirm, but some, such as variants in CACNA1H and the 15q13.3 microdeletion, are established.…”
mentioning
confidence: 99%
“…However, the mechanism of the disease-associated variants (single nucleotide polymorphisms, SNPs and/or copy number variations) in these channels and neurotransmitters is poorly understood. With the tremendous advance of technological development, the results of Genome-Wide Association (GWA) and candidate gene studies have suggested a few potential risk variants for epilepsy and encompass two broad categories reported in predominately Caucasian populations: 1) the genes/loci discovered in association with primary epilepsy syndromes; 2) the genes suggested in association with disorders of brain development that are associated with epilepsy [3]. However progress in extending beyond identification of disease-causing mutations and clarify disease pathophysiology mechanisms has been slow.…”
Section: Introductionmentioning
confidence: 99%
“…Single gene defects in ion channels or neurotransmitter receptors are associated withsome inherited forms of epilepsy [1][2][3][4][5][6]. In addition, genetic discoveries in the field of infantile epilepsy syndromes have highlighted the possible different aetiologies other than channelopathies can result in epilepsy [7].…”
Section: Introductionmentioning
confidence: 99%